Assessing and improving labour productivity management in construction: A practical framework and measurement tool - Nhat Minh Huynh; Long Le-Hoai; Chi Dien Do (Construction Economics and Building)
Despite numerous studies and resources available, the global construction sector has witnessed a decline in productivity over the past two decades, highlighting the need for practical tools and strategies to enhance labour productivity management. This study proposed a tool to support labour productivity management in construction. To achieve this, initial data were gathered through literature reviews and on-site observations, followed by interviews with ten experienced site managers to refine a comprehensive set of productivity factors. These factors were then used to construct a system of factors before developing a quantitative management tool, inclusive of a measurement scale and an instructive guide. Finally, this tool was evaluated by the experts using a 5-level Likert scale to ensure its practicality and accuracy. The results show that the tool offers a structured and informative approach to assess and enhance labour productivity in construction projects, thereby supporting managers in making informed decisions and improvements towards more successful project outcomes. The insights gained from this research contribute to the ongoing efforts to address labour productivity challenges in the construction industry, paving the way for future developments and enhancements in productivity management tools.